2015
DOI: 10.1371/journal.pone.0119225
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-153 Inhibits Osteosarcoma Cells Proliferation and Invasion by Targeting TGF-β2

Abstract: Increasing evidence indicates that microRNAs (miRNAs), a class of small noncoding RNAs, participate in almost every step of cellular processes. MiRNAs are aberrantly expressed in human cancers and contribute to cancer development and progression. Study of miRNAs may provide a new clue for understanding the mechanism of carcinogenesis and a new tool for cancer treatment. In the present study, miR-153 was downregulated in human osteosarcoma tissues and cell lines. Introduction of miR-153 mimics into the MG-63 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…2 Some studies have found that miR-153-3p can inhibit the proliferation and invasive growth of breast cancer and osteosarcoma cells. 9,10 These findings indicate that miR-153-3p can act as a tumor suppressor and may serve as a potential target for the treatment of malignant tumors. However, whether miR-153-3p regulates the proliferation of ESCC cells and confers sensitivity to cisplatin chemotherapy remains unclear.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 Some studies have found that miR-153-3p can inhibit the proliferation and invasive growth of breast cancer and osteosarcoma cells. 9,10 These findings indicate that miR-153-3p can act as a tumor suppressor and may serve as a potential target for the treatment of malignant tumors. However, whether miR-153-3p regulates the proliferation of ESCC cells and confers sensitivity to cisplatin chemotherapy remains unclear.…”
Section: Introductionmentioning
confidence: 93%
“…Upregulation of miR‐153 has been shown to inhibit the migration and invasion of ESCC cells, both in vitro and in vivo . Some studies have found that miR‐153‐3p can inhibit the proliferation and invasive growth of breast cancer and osteosarcoma cells . These findings indicate that miR‐153‐3p can act as a tumor suppressor and may serve as a potential target for the treatment of malignant tumors.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown to participate in the pathogenesis of neurodegenerative diseases, such as Parkinson's and Alzheimer's disease (Liang et al, 2012). Moreover, it was reported to inhibit the proliferation and invasion of many types of malignant cells, for example osteosarcoma and lung cancer cells (Niu et al, 2015). Thus, it is viewed as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was identified that miR-153 upregulation significantly suppressed TGF-β 2 and Smad2 protein expression of 13-9B cells. Niu et al (23) suggested that miR-153 inhibits osteosarcoma cell viability and invasion through targeting TGF-β 2 . Liang et al (24) also identified that miR-153 disturbs TGF-β 1 /p-SMAD2/3 signal transduction, acting as an anti-fibrotic element in the development of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%